Boundedness of Multilinear Commutators with Rough Kernels on Morrey-Herz Spaces (Analysis in Theory and Applications, 2013)
This paper is concerning the commutators generated by the multilinear singular integral with rough kernels and BMO functions. The boundedness of the multilinear commutators $T_{\vec{b}}(\vec{f})$ is established on the Morrey-Herz space by using the John-Nirenberg inequality.